THE IMPACT OF STRESS MANAGEMENT FOR URBAN MUSLIMS: INCREASING THE RESILIENCE OF SURVIVORS OF THE KANJURUHAN TRAGEDY - Mahmudah, Siti; Astutik, Fuji; Khoirot, Umdatul; Safitri, Rini (AKADEMIKA: Jurnal Pemikiran Islam, 2024)
One of the impacts of a disaster or tragedy is the presence of trauma after the event or a mental state that is shaken so that it is unable to survive with a healthy mentality. This research aims to help Muslim urban communities who are victims of the Kanjuruhan tragedy through the provision of the Impact of stress management to increase resilience. In this study, the researcher used a quantitative approach with the quasi-experimental method of one group pretest post-test to test the effect of treatment before and after treatment. The participants were 19 (3 victims were directly affected, and 16 were indirectly affected). Data were collected through questionnaires before and after the administration of treatment, as well as long-term monitoring. The results showed a significant difference in participants’ resilience levels before and after being given the Impact of stress management. The effect size caused by these activities is relatively large when viewed from the average resilience ratio before and after activities. Likewise, the significance test that shows a significant impact is shown by a significance number of 0.000, which is < out of 0.05. This study concludes that the Impact of stress management is practical and has a significant effect on increasing the resilience of the participant.